The Influence Of Human Resource Management Strategies On Teacher Quality Through The Learning Process In Schools - Olang, Stela; Kuncono, Setio; Nafisah, A'isy Fiklil; Sumunu, Trenggono; Handayani, Sari (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of human resource management (HR) strategies on the quality of teachers through the learning process in schools. This study examines how various HR management strategies, such as recruitment, training, development, performance appraisal, and compensation, affect teacher quality. The quality of teachers is measured through pedagogic, professional, social, and personality competencies. The learning process is evaluated based on the interaction of teachers and students, the use of innovative learning methods, and the achievement of student learning outcomes. The study also considers contextual factors such as the work environment, the principal's support, and school resources that can moderate the relationship between HR management strategies and teacher quality. This study uses a quantitative approach with a survey method. Data was collected through questionnaires. Data analysis was carried out using statistical techniques such as regression and analysis. The results of the study are expected to provide insight for school managers and policymakers on the importance of HR management strategies, as well as provide practical recommendations for schools and education stakeholders to optimize HR management strategies in improving teacher quality and creating an effective learning environment. Thus, this research contributes to the development of better education through improving the quality of teacher human resources.